Why Bother with the Scholarship of Teaching and Learning? - John Draeger (Park University, 2013)
This paper argues that the scholarship of teaching and learning (SoTL) matters on at least six interrelated levels. First, SoTL matters because learning matters, and SoTL can help students learn more effectively. Second, it offers professors the tools to more effectively share their disciplinary passions. Third, it offers faculty an avenue for continued intellectual growth. Fourth, SoTL can build strong crossdisciplinary communities that enliven the intellectual climate. Fifth, it can inform institutional policymaking. Finally, SoTL matters even when it does not directly transform institutional policy, because SoTL embodies a spirit of pedagogical innovation that enlivens the quest for learning and reminds us why it is worth pursuing.